The Relationship Between Ankle Angle at Initial Contact and Shin Splints in Recreational Runners - Sepfiana, Gerarda; Herawati, Isnaini (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
Running is a sport prone to causing injuries, particularly in recreational runners. One common injury is shin splints, characterized by pain in the lower leg often caused by running activities. This study aims to analyze the relationship between ankle angle during initial contact and shin splint severity in recreational runners. A cross-sectional design with an analytical observational approach was used. The sample included 27 recreational runners meeting specific inclusion criteria. Measurements were conducted using the Shin Pain Scoring System to evaluate shin splint severity and the Apecs application to measure ankle angle at initial contact. The data analysis used is Shapiro-Wilk for normality test and Pearson for correlation. The results indicate a significant relationship between ankle angle during initial contact and shin splint severity (p < 0.05). These findings suggest that improper ankle angles during initial ground contact may increase the risk of shin splints in recreational runners. This study highlights the importance of proper running techniques to prevent injuries, especially shin splints.